Programming Elixir functional - concurrent - pragmatic - fun - Thomas, David (Pragmatic Bookshelf, 2014)
This book is your guide to Elixir, a modern, functional, and concurrent programming language. By the end of this book, you'll understand Elixir, and know how to apply it to solve your complex, modern problems.